Pengaruh Beban Kerja, Pemahaman Teknologi Informasi Dan Kompetensi Terhadap Kinerja Pegawai Pengelola Dana Alokasi Khusus (Dak) Pemerintah Provinsi Kepulauan Riau Dengan Komitmen Organisasi Sebagai Variabel Intervening - Endang Irmarita, Yani; Wibisono, Chablullah; Gita Indrawan, Mohamad (Program Studi Manajemen FEBM UMRAH, 2024)
The realization of DAK in Riau Islands Province shows a fluctuating trend, namely the fluctuation of the DAK ceiling and budget. Based on the above phenomenon, the reporting of Special Allocation Funds is based on the principle of accountability and commitment and quality of human resources in carrying out tasks and understanding of the OM SPAN application is also important in the management of DAK Province. The purpose of this study was to analyze the Workload on the performance of DAK managers intervening with organizational commitment in Riau Islands Province. Analyze Competence on the performance of DAK managers intervening with organizational commitment in Riau Islands Province. Analyze Mastery of Information Technology on the performance of DAK managers intervening with organizational commitment in Riau Islands Province. The testing of the research hypothesis was carried out using the Structural Equation Model (SEM) approach based on Partial Least Square (PLS). PLS is a structural equation model (SEM) based on components or variants. The results of the study In the relationship between Workload (X1) and Performance (Y) there is a significant relationship in the model. The results of this study can be concluded that high Workload intervening with organizational commitment has an effect on Performance. The results of this study can be concluded that Competence intervening by Organizational Commitment has an effect on Work. It can be interpreted that the original sample has a positive value, meaning that there is a positive relationship in the model. The results of this study can be concluded that Mastery of Information Technology intervening by Organizational Commitment has an effect on Performance.